1999
DOI: 10.1046/j.1523-1755.1999.00493.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and biochemical correlates of starting “daily” hemodialysis

Abstract: These results suggest that in certain patients, daily hemodialysis might have advantages over three times per week hemodialysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
144
0
10

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(163 citation statements)
references
References 14 publications
9
144
0
10
Order By: Relevance
“…Also, subscales of PCS and MCS, except mental health and social functioning subscales which revealed only a trend, were significantly linked to mortality. Consistent with other reports, we described that serum albumin was one of the strongest independent predictors of patient outcome (5,6,14,15). In this study, we showed that the ideal serum albumin was higher than 4 g/dL, and the risk of death was respectively 3.7, 2.1, and 1.9 folds in patients with the serum albumin ≤ 3.60 g/dL (the lowest quintile), > 3.60 -3.85 g/dL, and > 3.85 -4.00 g/dL compared to patients with serum albumin of more than 4.20 g/dL (the highest quintile).…”
Section: Discussionsupporting
confidence: 91%
“…Also, subscales of PCS and MCS, except mental health and social functioning subscales which revealed only a trend, were significantly linked to mortality. Consistent with other reports, we described that serum albumin was one of the strongest independent predictors of patient outcome (5,6,14,15). In this study, we showed that the ideal serum albumin was higher than 4 g/dL, and the risk of death was respectively 3.7, 2.1, and 1.9 folds in patients with the serum albumin ≤ 3.60 g/dL (the lowest quintile), > 3.60 -3.85 g/dL, and > 3.85 -4.00 g/dL compared to patients with serum albumin of more than 4.20 g/dL (the highest quintile).…”
Section: Discussionsupporting
confidence: 91%
“…[5][6][7][8] Two nonrandomized studies suggested that, compared with conventional dialysis, daily dialysis is associated with a five-fold decrease in access complications. 9,10 However, two literature reviews suggested the opposite. 11,12 These reviews highlighted two North American nonrandomized studies that reported a trend to doubling of access interventions in patients receiving daily hemodialysis with arteriovenous fistulae.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a multicenter study of 72 patients who used frequent HD from 1972 to 1996, Woods et al reported that the most common reason given for patients starting frequent HD was lifestyle or employment (24). In the 2004 ESRD Facility Survey, 122 units reported that patients received frequent incenter HD during the day, 19 reported that patients received frequent home HD during the day, 2 reported that patients received in-center nocturnal HD, and 8 reported that patients received home nocturnal HD.…”
Section: Discussionmentioning
confidence: 99%